Diagnóstico sectorial de la subclase actividades de laboratorios médicos del cantón Loja - Torres Gualán, Luis Damián (2023)
A sectorial diagnosis is an organized and systematic method that uses observations and concrete data to obtain statistical information on the companies in the sector and establish industry averages; it is essential for companies to measure their performance against competence. The objective of this research is to carry out a sectorial diagnosis of the medical laboratory activities of the Loja canton, for which 42 medical laboratories classified with the ISIC code Q8690.2 were studied, which provide their services within the geographical limits of the canton. The research was carried out with a mixed approach of exploratory, field, and descriptive type because there are no antecedents of similar research. In order to gather the necessary information, direct observation of the laboratories, bibliographic review, and the application of surveys to laboratory managers and owners were carried out; the information was studied, ordered, and synthesized to define the characteristics, statistics, and averages of the sector; with the application of the winsorizing technique to reduce the impact of atypical data and guarantee the reliability of the data. The relevant results indicated that the critical success factors are demand, continuous improvement and innovation, quality of service, employees, and financial resources, while the financial indicators showed the following results: ROA 0.15, ROE, 0.32 net profit margin 0.16, etc.; and among the non-financial indicators, the performance per employee of $ 38.45, advertising efficiency $ 30.39, ratio of doctors/analysis equipment 0.34 were highlighted. It was concluded that are currently 42 laboratories operating in Loja, 50% of which are above industry averages, demonstrating that the sector is competitive.